A decade of shaking in the Garden City: the dynamics of preparedness, perceptions, and beliefs in Canterbury, New Zealand, and implications for earthquake information - Becker, Julia S.; Vinnell, Lauren J.; Doyle, Emma E. H.; McBride, Sara K.; Paton, Douglas; Johnston, David M. (Frontiers in Communication, 2024)
The final, formatted version of the article will be published soon.